Table of Content - -, (Journal of Economic, Administrative and Legal Sciences, 2023)
Table of Content:1. Evaluating the Performance of Internal Control under the Electronic Accounting System in Saudi Private Universities. Case Study of Private Colleges in Gassim 2021Dr. Adil Mohamed Ahmed Yousif2. The importance of accounting disclosure of social responsibility  And its impact on achieving sustainable development by applying to the Saudi Paper Manufacturing Company in the Kingdom of Saudi Arabia (case study from 2021-2022)Dr. Salwa Hussien Roshdy Ismaiel3. The Impact of Financial and Operating Leverage on Profitability of Industrial Companies listed  on Saudi Stock Exchange Market (During 2017-2021)Co-Prof. Ahmed Hashim Ahmed4. Foreign direct investment and its impact on industry in Kingdom of Saudi Arabiasystematic reviewDr. Vivian Mohammed Saleh Nasrulddin, Mrs. Bayan Khalaf Al-Juaid, Mrs. Kholoud Bakheet Misfer Al-Ghamdi, Mrs. Tharaa Hassan Omar Al-Idrisi5. Monetary policy and its impact on achieving economic stability in Yemen for the period  (1990-2004)Mr. Yahya Ali Yahya Al-Sqqaf6. The Impact of the Work Environment on the Performance of Nurses in the Saudi Healthcare SectorMr. Khalid Mansour Althobaiti, Mrs. Amani Hassan Altherwi, Mrs. Haya Ali Almbrook, Mrs. Abrar Fawaz Alfayz, Mr. Obaid Ali Alkhairi, Mr. Ali Hassan Mohammed Alrashdi4, Mr. Balker Muhammad Abdullah,  Mrs. Badrah Ibrahim Alzubaidi, Mr. Abdullah Ali Hamzah Alkhiri, Mr. Faris Sulaiman Aljaloud7. Anonymizing witnesses in Federal Law No. (14) of (2020 AD) Concerning the protection  of witnesses and the likeDr. Rashed Abdulla Ahmed Faridi Almarzooqi8. The role of knowledge management in improving professional relations– A field study on administrative staff in the Emirate of Makkah Al-Mukarramah Region - in Jeddah –Mrs. Ruwayna Talal Midad